The effect of MiR-497 on the expression of target genes BCL-2 and LC3B on cardiomyocytes injured by hypoxia/reoxygenation: MiR-497 effects on the BCL-2 and LC3B - Zhang, Hua’an; Ye, Wanhao; Li, Yingpu (Cellular and Molecular Biology, 2022)
Myocardial ischemia is easy to cause hypoxia or necrosis of myocardial cells. At present, the performance of various patients is different. Basically, it is mainly caused by chest pain or chest discomfort. Severe patients may die suddenly. Therefore, looking for effective drugs or methods to prevent and treat Cardiomyocyte injury is of great significance for clinical practice, in which the expression of regulatory gene BCL-2 and microtubule-associated protein light chain 3B (LC3B) has a certain effect on hypoxia/reoxygenation injured cardiomyocytes. To this end, the team designed a study on the effect of miR-497 on the expression of target genes BCL-2 and LC3B on cardiomyocytes injured by hypoxia/reoxygenation. In this study, a control group experiment was set up for the study. During the experiment, the cells were treated with hypoxia-reoxygenation and transfected with the corresponding miR-497 treated cells. By detecting apoptosis, the kit was used to detect cell activity and RT-PCR detection. Gene expression levels and other methods are comparatively judged. The results of this study showed that compared with the normal group 14.50±0.78, the viability of cardiomyocytes in the model group was significantly reduced (P<0.01), the amount of NO released by cardiomyocytes was reduced (P<0.01), and the protein expression in cardiomyocytes was significantly reduced (P<0.01). The experimental results of this study prove that miR-497 can alleviate the damage caused by hypoxia-reoxygenation of cardiomyocytes by regulating target genes BCL-2 and LC3B.